TARI JARAN GOYANG: SIMBOL PEMIKAT ASMARA - Suharti, Mamik (Institut Seni Indoensia Surakarta, 2014)
The genre of dance called Jaran Goyang is one of the tradition dance genres in Banyuwangi. Thisdance is composed by Suparman in 1960. Furthermore, Banyuwangi and more work of dances arecomposed by him. Jaran Goyang dance is a tradition dance with romantic theme. This movementrefers to tradition dance previously; it includes its music and ricikan. The name of this dance comesfrom love magical formula called Jaran Goyang (shaky horse). The choreography of dance is basedon the denied love by a female dancer. However, the female dancer is falling in love unexpectedly dueto love magical formula called Jaran Goyang. Jaran Goyang dance is divided into some Susana in itsperformance. It illustrates a love story between a male and a female which is full of problems inside.Keywords: Dance, Jaran Goyang, Symbol, Entice, Romantic love.